Application of Diffusion-Weighted Imaging in the Detection of Active Sacroiliitis and the Comparison of Apparent Diffusion Coefficient and Relative Apparent Diffusion Coefficient Values - İclal Erdem TOSLAK,; Meral BİLGİLİSOY FİLİZ,; Bülent ÇEKİÇ,; Ayşe Eda PARLAK,; Hasan Fatih ÇAY,; Sevim YILDIZ,; Bekir EROL,; Deniz ÖZEL,; İlhan SEZER, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the role of diffusion-weighted imaging in detection of active sacroiliitis and compare the apparent diffusion coefficient (ADC) and normalized relative ADC (r-ADC) values by using vertebra and iliac wings as reference organs. Patients and methods: The study included 56 patients (26 males, 30 females; mean age 37.7±10.1 years; range 18 to 66 years) with chronic back pain and without history of sacroiliitis who underwent magnetic resonance imaging. T2-weighted spectral presaturation with inversion recovery, contrast-enhanced T1-weighted spectral presaturation with inversion recovery, and diffusion-weighted (b values: 0 and 600 s/mm2) images were obtained. All images were evaluated by two different radiologists for interobserver variability. All individuals were grouped in either mechanical low back pain (control group) or active sacroilitis (disease group) groups according to the presence or absence of MRI findings of active sacroilitis. ADC values of both surfaces were measured from normal and affected areas of joints. Also, ADC values of L5 vertebra and iliac wings were measured as reference organs to calculate r-ADC values. Results: Mean ADC and r-ADC values measured from lesions were significantly higher than that of normal appearing bone marrow areas in both patients with mechanical low back pain (n=17) and active sacroiliitis (n=39). Both ADC values and r-ADC values could differentiate active lesions from normal appearing bone marrow areas as well as contrast-enhanced T1-weighted images. According to r-ADC values calculated with the L5 vertebra, unaffected portions of bone marrow areas in patients with sacroiliitis were normalized whereas r-ADC remained higher than normal in affected portions of the bones. Conclusion: Diffusion-weighted imaging is a fast, sensitive magnetic resonance imaging sequence in detection of active sacroiliitis. It does not require contrast agent and can be safely used as an adjunct to conventional magnetic resonance images. r-ADC is also highly sensitive in detecting active sacroiliitis and may be used as an alternative to standard ADC measurements for the demonstration of inflammation. It helps eliminate individual bone marrow differences by using patients’ own normal bone marrow measurements and increases diagnostic accuracy.